2018
DOI: 10.3389/feduc.2018.00032
|View full text |Cite
|
Sign up to set email alerts
|

“The Rules of Engagement”: Student Engagement and Motivation to Improve the Quality of Undergraduate Learning

Abstract: Studying at university continues to grow in popularity and the modern-day university has expanded considerably to meet this need. Invariably as such expansion occurs pressures arise on a range of quality enhancement processes. This may have serious implications for the continued delivery of high quality learning experiences that both meet the expectations of incoming students and are appropriate to their postgraduation aspirations. Ensuring students become active partners in their learning will encourage them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…This is similar to the experience of students in Harvard school of dental medicine who perceived the virtual learning live lecture synchronous approach to increase burnout and decrease student retention and engagement with course content (Chen, Kaczmarek, & Ohyama, 2020). Therefore, it is of crucial importance to provide students with the opportunity to share their opinions and voice their concerns which has been perceived as an important driver for student engagement (Senior et al, 2018). The CPH administration met with student leaders several times during the spring semester 2020.…”
Section: Covid-19 Special Collectionmentioning
confidence: 59%
“…This is similar to the experience of students in Harvard school of dental medicine who perceived the virtual learning live lecture synchronous approach to increase burnout and decrease student retention and engagement with course content (Chen, Kaczmarek, & Ohyama, 2020). Therefore, it is of crucial importance to provide students with the opportunity to share their opinions and voice their concerns which has been perceived as an important driver for student engagement (Senior et al, 2018). The CPH administration met with student leaders several times during the spring semester 2020.…”
Section: Covid-19 Special Collectionmentioning
confidence: 59%
“…As this is a 'borderline' subscale positioned in the middle of the self-determination continuum, it was plausible to expect neither relation with the SAES scores. It is important to underline that this is an important finding as many studies have proven that academic engagement is associated with the students' motivation (e.g., Appleton et al, 2008;Senior et al, 2018) and that some motivational antecedents may encourage academic engagement (Wang & Eccles, 2013;Wang & Holcombe, 2010). This implies the possibility to adopt the SAES for evaluating university interventions aimed at improving academic engagement and students' retention, by also assessing if such interventions promote more autonomous forms of students' motivation.…”
Section: Discussionmentioning
confidence: 97%
“…To develop some of the items we resorted to available motivation scales (as the intrinsic motivation inventory) since students' motivation can be considered as another influential factor for engagement. Prior studies have also thoroughly shown that engagement is associated with the motivation (e.g., Alivernini et al, 2017;Appleton et al, 2008;Senior et al, 2018). Example items are: The course of study I am attending is interesting or I like the course of study I'm attending.…”
Section: Development Of the Saes Instrumentmentioning
confidence: 99%
See 2 more Smart Citations